Adsorption and Photocatalytic Processes of Mesoporous SiO2-Coated Monoclinic BiVO4 - Channei, Duangdao; Nakaruk, Auppatham; Khanitchaidecha, Wilawan; Jannoey, Panatda; Phanichphant, Sukon (Frontiers in Chemistry, 2018)
The silicon dioxide (SiO2)–coated bismuth vanadate (BiVO4) composites as visible–driven–photocatalysts were successfully synthesised by the co–precipitation method. The effects of SiO2 coating on the structure, optical property, morphology and surface properties of the composites were investigated by X–ray diffraction (XRD), UV–visible diffuse reflectance spectroscopy (DRS), transmission electron microscopy (TEM) and Brunauer–Emmette–Teller (BET) measurements. The photocatalytic activity of monoclinic BiVO4 and BiVO4/SiO2 composites were evaluated according to the degradation of methylene blue (MB) dye aqueous solution under visible light irradiation. The SiO2–coated BiVO4 composites showed the enhancing photocatalytic activity approximately threefold in comparison with the single phase BiVO4.